The Influence of the SAVI Model on Students' Motivation and Learning Outcomes in Social Studies at Madrasah Tsanawiyah - Indriansyah, Renata Tiand; Amin, Saiful (Journal of Education on Social Science (JESS), 2025)
This study aims to analyze the effect of the SAVI (Somatic, Auditory, Visualization, Intellectual) learning model on: (1) students' learning motivation and (2) students' learning outcomes in Social Studies. This model was implemented to enhance student engagement in learning and to assess its effectiveness compared to conventional methods. This research employs a quantitative approach with a quasi-experimental non-equivalent control group design. The subjects of the study were eighth-grade students at MTs Almaarif 02 Singosari Malang, divided into an experimental class and a control class. The experimental class received instruction using the SAVI learning model, while the control class was taught using the lecture method. Data were collected through motivation questionnaires and learning outcome tests. Statistical analysis was conducted using normality tests, homogeneity tests, and N-Gain tests to measure learning improvement. The results indicate that: (1) the SAVI learning model positively influences students' learning motivation, as they became more active and demonstrated greater enthusiasm in the learning process and (2) the SAVI learning model significantly improves students' learning outcomes compared to conventional methods, as evidenced by increased comprehension and academic achievement. Based on these findings, it is recommended that teachers implement the SAVI learning model as an innovative strategy to enhance students' motivation and learning outcomes. Future research can explore the effectiveness of this model across different subjects and educational levels.